Ideas of Southern Africanism: Portugal and the Movements of Liberation (1961-1974) - Fonseca, Helder Adegar (2014)
In this paper we explored a crucial phase of “Southern African Liberation” era, between 1960-1974, as a driving force of the Southern African regional transnationalism, both «White» and African ways. It will be scrutinized one particular dimension: the progress of the Ideas of Southern Africa, as a particular political «region», within the Portuguese colonial Rule and Angola Liberation Movements (LMs). The variants and the pace of the idea of Southern Africa will be explored through text analysis, on the one hand, of the Portuguese politico-military reports produced since 1950s, on the other hand, the MPLA documents preserved and edited by Lúcio Lara ( 1951-1968) and “Radio Propaganda” promoted by the Angolan Movements of Liberation. I try to show that between 1968 and 1970 becomes clear competition between an “experienced” idea of an “African” Southern Africa 'African', carried by LMs , and not just an idea but also a project of a «White Southern Africa”, ie, under white leadership.